Group problem management plus (gPM+) in the treatment of common mental disorders in Syrian refugees in a Jordanian camp: study protocol for a randomized controlled trial - Aemal Akhtar; Luana Giardinelli; Ahmad Bawaneh; Manar Awwad; Hadeel Naser; Claire Whitney; Mark J. D. Jordans; Marit Sijbrandij; Richard A. Bryant; on behalf of the STRENGTHS Consortium (BMC Public Health, 2020)
Abstract Background Accessing quality mental health care poses significant challenges for persons affected by adversity, especially in low- and middle-income countries where resources are scarce. To mitigate this, the World Health Organization has developed group problem management plus (gPM+), a low-intensity psychological intervention for adults experiencing psychological distress. gPM+ is a group-based intervention consisting of five-sessions, and can be delivered by non-specialist providers. This paper outlines the study protocol for a trial of gPM+ in Jordan. Methods We will conduct a single-blind, two-arm, randomized controlled trial in a Syrian refugee camp in Jordan. We aim to enrol 480 adults into the trial. Participants will be eligible for the trial if they screen positive for levels of psychological distress. Following screening, those eligible will be randomly assigned to receive the gPM+ intervention or enhanced treatment as usual. The primary outcome is reduction in levels of psychological distress at 3-months post-treatment. Secondary outcomes include anxiety, depression, prodromal psychotic symptoms, posttraumatic stress disorder, prolonged grief, daily functioning, economic effectiveness, and change in parenting behaviour. Secondary outcomes also include the reduction in psychological distress of the participant’s child. Discussion The trial aims to deliver a template for affordable and scalable psychosocial interventions that can readily be implemented in refugee settings, and that can benefit both the participant and their child. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12619001386123 . Registered prospectively on 10/10/2019.